Atractylenolide III Attenuates Angiogenesis in Gastric Precancerous Lesions Through the Downregulation of Delta-Like Ligand 4 - Gao, Ying; Wang, Jundong; Zhao, Maoyuan; Xia, Ting; Liu, Qingsong; Chen, Nianzhi; Liao, Wenhao; Zeng, Zhongzhen; You, Fengming; Zeng, Jinhao (Frontiers in Pharmacology, 2022)
Background: Blocking and even reversing gastric precancerous lesions (GPL) is a key measure to lower the incidence of gastric cancer. Atractylenolide III (AT-III) is a mainly active component of the Atractylodes rhizome and has been widely used in tumor treatment. However, the effects of AT-III on GPL and its mechanisms have not been reported. Methods: H&E staining and AB-PAS staining were employed to evaluate the histopathology in the gastric mucosa. In parallel, CD34 immunostaining was performed for angiogenesis assessment, and transmission electron microscope for microvessel ultrastructural observation. Investigation for the possible mechanism in vivo and in vitro was conducted using immunohistochemistry, RT-qPCR and western blotting. Results: In most GPL specimens, AT-III treatment reduced microvascular abnormalities and attenuated early angiogenesis, with the regression of most intestinal metaplasia and partial dysplasia. Meanwhile, the expression of VEGF-A and HIF-1α was enhanced in GPL samples of model rats, and their expressions were decreased in AT-III-treated GPL rats. Moreover, DLL4 mRNA and protein expression were higher in GPL rats than in control rats. DLL4 protein expression was significantly enhanced in human GPL tissues. In addition, AT-III treatment could diminish DLL4 mRNA level and protein expression in the MNNG-induced GPL rats. In vitro study showed that in AGS and HGC-27 cells, DLL4 mRNA level and protein expression were significantly decreased after AT-III treatment. However, AT-III had no significant regulatory effect on Notch1 and Notch4. Conclusions: AT-III treatment is beneficial in lessening gastric precancerous lesions and attenuating angiogenesis in rats, and that may be contributed by the decrease of angiogenesis-associated HIF-1α and VEGF-A, and downregulation of DLL4.